INISIASI PEMERINTAH INDONESIA TERKAIT ISU CYBER CRIME YANG MENGHASILKAN KESEPAKATAN CODE OF CONDUCT ON FRAMEWORK FOR SECURITY COOPERATION DENGAN PEMERINTAH AUSTRALIA (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
This study to describe issue which resulted in an agreement on the Code of Conduct on the Framework for Security Cooperation. The findings in this study are the issue of cyber crime that is currently happening in Indonesia has a negative impact on relations between Indonesia and Australia. The issue of cyber crime can be explored through a theory that offers a framework to discuss the agenda setting process. The agenda setting saw that there were three things contained in the espionage case that occurred to the former President of the Republic of Indonesia, Susilo Bambang Yudhoyono. First, the public agenda is the focus of attention in a certain period. Second, the policy agenda is an agreement or arrangement made by a group of people. Third, the media agenda is the focus of attention on a certain period. Keywords: Cyber ??Crime, Agenda Setting, Agreement, Code of Conduct